Potential for use of polyploidy in Eucalyptus breeding programs - Souza, Thaise da Silva (2021)
The induction of polyploidy in Eucalyptus can be one of the alternatives to boost eucalypt breeding since additional gains through conventional plant breeding may not meet new production demands. After artificial polyploidization, it is necessary to certify the effectiveness of the duplication via cytogenetic analyses, including chromosomal counts and nuclear DNA quantification. Another alternative is to indirectly evaluate the chromosome duplication by detecting changes in anatomical and morphological traits, such as stomata and leaf area measures, and wood anatomy studies. Besides, the confirmation of the clone performance in field conditions is essential to validate the importance of this technique. This study aimed: i) to certify the chromosome duplication in artificially polyploidized clones, using cytogenetic analysis, flow cytometry, and leaf anatomy measurements; ii) to compare the performance of Eucalyptus diploid and polyploid clones with the same genetic origin by analyzing the physical and anatomical properties of the wood to provide more information on wood quality for pulp and paper production; and iii) to evaluate the performance of these clones under field conditions to verify if they are more adapted and stable for forest exploration, and if the performance of polyploid depends on its diploid of origin. Clones of Eucalyptus grandis x Eucalyptus urophylla diploids and artificial polyploids produced by Suzano SA were evaluated. Chromosomal counts and DNA content estimation allowed the identification of artificially polyploidized clones and mixoploids. Polyploid clones presented larger stomata diameter than diploids and leaf area significantly increased as a function of the ploidy level. Wood samples from these hybrids were analyzed and the results suggested that polyploid eucalypt clones presented lower basic density and fibers with higher length and wall thickness than diploids, which improves fiber accommodation in the paper formation and increases its strength, indicating the potential use of polyploids in eucalypt pulp and paper production. Measurements of DBH (diameter at breast height) and MAI (mean annual increment) of three-year-old trees were evaluated and the analyzes allowed to verify that polyploids differed in adaptability and stability, and in most cases, they exhibit lower performances than diploids. The relative behavior of polyploid clones does not depend on the performance of the diploid that originated it since the most adapted polyploid clones were originated from the diploid clone with the lowest performance. These results indicate that the potential for use of polyploids in eucalypt breeding is promising, although there is a need for more studies to answer the questions that remain.